TINGKAT VO₂ MAX SEBAGAI INDIKATOR KEBUGARAN FISIK PERSONEL PKP-PK YIA - Antonius Agus Medinugroho; Ichyu Machmiyana; Ahmad Faridan Juniawan (LPPM Politeknik Pratama, 2025)
Physical fitness is a crucial factor in supporting the effectiveness of Airport Rescue and Firefighting (ARFF) personnel, particularly in emergency situations at the airport. One physiological indicator used to objectively measure physical fitness is VO₂ Max, which refers to the body’s maximum capacity to utilize oxygen during high-intensity physical activity. This study aims to analyze VO₂ Max levels as an indicator of physical fitness among ARFF personnel at Yogyakarta International Airport, using a descriptive quantitative method with a total sampling technique involving 70 active personnel. Measurements were conducted through the Multistage Fitness Test (beep test) and classified based on established fitness standards, showing that 37.1% were in the “good” category, 24.3% in “fair”, 24.3% in “poor”, 12.9% in “very poor”, and only 1.4% in “very good”, with none achieving the “excellent” category. These findings indicate that most personnel have not reached the optimal fitness level required for high-risk operational duties, and therefore recommend optimizing VO₂ Max-based physical training programs to improve operational readiness and workplace safety in the airport environment.